Governance and innovation policy failures in Europe. Issue 3 (12th March 2013) - Schepers, Stefan
Abstract : It is axiomatic in business management that organization follows strategy. In public policy, it is not different: governance organization and tools are dependent on the objectives that authorities want to achieve. The present stagnation, if not decline, of the European Union provides an interesting warning not to ignore this. Copyright © 2013 John Wiley & Sons, Ltd.